2018
DOI: 10.3390/antiox7030042
|View full text |Cite
|
Sign up to set email alerts
|

Redistribution of Extracellular Superoxide Dismutase Causes Neonatal Pulmonary Vascular Remodeling and PH but Protects Against Experimental Bronchopulmonary Dysplasia

Abstract: Background: A naturally occurring single nucleotide polymorphism (SNP), (R213G), in extracellular superoxide dismutase (SOD3), decreases SOD3 matrix binding affinity. Humans and mature mice expressing the R213G SNP exhibit increased cardiovascular disease but decreased lung disease. The impact of this SNP on the neonatal lung at baseline or with injury is unknown. Methods: Wild type and homozygous R213G mice were injected with intraperitoneal bleomycin or phosphate buffered saline (PBS) three times weekly for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…Secondly, we did not detect clear reductions in HA content or fragment size in wildtype mice during the course of chronic hypoxia. This implies that hypoxic HA fragmentation itself may not be a sufficient disease trigger, but that it may exacerbate or accelerate PH in susceptible backgrounds of altered extracellular redox status due to impaired SOD3 expression 10 , activity 66 , or localization 6,67 . Since our gel separation methods cannot resolve very low molecular weight and oligomeric HA species (≤50 kDa), we may have not captured the formation of these bioactive fragments in the lung tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, we did not detect clear reductions in HA content or fragment size in wildtype mice during the course of chronic hypoxia. This implies that hypoxic HA fragmentation itself may not be a sufficient disease trigger, but that it may exacerbate or accelerate PH in susceptible backgrounds of altered extracellular redox status due to impaired SOD3 expression 10 , activity 66 , or localization 6,67 . Since our gel separation methods cannot resolve very low molecular weight and oligomeric HA species (≤50 kDa), we may have not captured the formation of these bioactive fragments in the lung tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Alteration in ECSOD expression is associated with disease in these tissues, and polymorphisms of ECSOD have been identified to contribute to lung and cardiovascular disease. In the primary article by Sherlock et al [ 14 ], the authors show that a polymorphism of ECSOD, R213G, results in more ECSOD in the serum and less ECSOD bound to the vasculature. The R213G ECSOD mice have abnormal pulmonary vascular development but are better protected from lung injury.…”
mentioning
confidence: 99%
“…Chen et al recently found that SOD activity in BPD mice was decreased with the enhancement of MDA level [ 20 ], which is consistent with our findings. In a related research, it was discovered that increased SOD activity could treat lung damage and hypertension in BPD patients [ 21 ]. It was reported that enhancement of MDA level triggered hyperoxia-induced oxidative stress, which aggravated lung damage and impeded vascular and pulmonary tissue growth [ 22 ].…”
Section: Discussionmentioning
confidence: 99%